Gut microbiome composition of wild western lowland gorillas is associated with individual age and sex factors - Pafčo, Barbora; Sharma, Ashok K; Petrželková, Klára J; Vlčková, Klára; Todd, Angelique; Yeoman, Carl J; Wilson, Brenda A; Stumpf, Rebecca; White, Bryan A; Nelson, Karen E; Leigh, Steven; Gomez, Andres (American journal of physical anthropology, 2019)
OBJECTIVES: Environmental and ecological factors, such as geographic range, anthropogenic pressure, group identity, and feeding behavior are known to influence the gastrointestinal microbiomes of great apes. However, the influence of individual host traits such as age and sex, given specific dietary and social constraints, has been less studied. The objective of this investigation was to determine the associations between an individual's age and sex on the diversity and composition of the gut microbiome in wild western lowland gorillas. MATERIALS AND METHODS: Publicly available 16S rRNA data generated from fecal samples of different groups of Gorilla gorilla gorilla in the Central African Republic were downloaded and bioinformatically processed. The groups analyzed included habituated, partially habituated and unhabituated gorillas, sampled during low fruit (dry, n = 28) and high fruit (wet, n = 82) seasons. Microbial community analyses (alpha and beta diversity and analyses of discriminant taxa), in tandem with network-wide approaches, were used to (a) mine for specific age and sex based differences in gut bacterial community composition and to (b) asses for gut community modularity and bacterial taxa with potential functional roles, in the context of seasonal food variation, and social group affiliation. RESULTS: Both age and sex significantly influenced gut microbiome diversity and composition in wild western lowland gorillas. However, the largest differences were observed between infants and adults in habituated groups and between adults and immature gorillas within all groups, and across dry and wet seasons. Specifically, although adults always showed greater bacterial richness than infants and immature gorillas, network-wide analyses showed higher microbial community complexity and modularity in the infant gorilla gut. Sex-based microbiome differences were not evident among adults, being only detected among immature gorillas. CONCLUSIONS: The results presented point to a dynamic gut microbiome in Gorilla spp., associated with ontogeny and individual development. Of note, the gut microbiomes of breastfeeding infants seemed to reflect early exposure to complex, herbaceous vegetation. Whether increased compositional complexity of the infant gorilla gut microbiome is an adaptive response to an energy-limited diet and an underdeveloped gut needs to be further tested. Overall, age and sex based gut microbiome differences, as shown here, maybe mainly attributed to access to specific feeding sources, and social interactions between individuals within groups.
Keywords: DNA, Bacterial; střevní mikroflóra; RNA, Ribosomal, 16S; microbiome; sex; zvířata; feces; Gastrointestinal Microbiome; RNA ribozomální 16S; DNA bakterií; mužské pohlaví; Feces; Aging; Gorilla; Sex Factors; antropologie fyzická; Gorilla gorilla; ženské pohlaví; sexuální faktory; Animals; Anthropology, Physical; Male; age; stárnutí; Female